Comparative Analysis of Food Expenditure Pattern of Nepalese Households Using Engel Curves - Khanal, Bishu; Banskota, Kamal; Giri, Dhiraj (Journal of Business and Social Sciences Research, 2018)
The study examined the effects of demographic and non-demographic factors like income, family size, rural/urban location of household and gender of household head on consumption expenditure across 9 different food commodities. To analyze the food consumption behavior of Nepalese households National Living Standard Survey (NLSS) over two years 1995/96 and 2010/11 have been used. This study found that there have been significant changes in food consumption pattern in Nepal during these two periods. Food budget share of a household has declined over time. Budget share of cereals and pulses has shifted towards other food items such as fruits, vegetables, meat, dairy products and other miscellaneous food items. Result also shows that lower income households have higher expenditure elasticities of food compared to higher income households. Similarly, rural households have higher expenditure elasticities of food compared to urban households. For male and female headed households, expenditure elasticities are almost similar for major food categories. Diseconomies of scale are found in food expenditure as an additional family member would increase additional expenditure on food. The findings of this study are significant as they would serve as important policy guidelines and basis for further studies.Journal of Business and Social Sciences Research, Vol. 2, No. 1 & 2, pp. 27-46